Combined Effects of Multiple Stressors: New Insights Into the Influence of Timing and Sequence - Brooks, Paul R.; Crowe, Tasman P. (Frontiers in Ecology and Evolution, 2019)
Complex regimes of stress arise when multiple stressors combine simultaneously, with varying degrees of temporal separation or variation in their sequential order. A manipulative field experiment was run to test whether doses of two stressors (Copper and Biocide) varied in their effects on marine epifauna and ecosystem functioning depending on their sequence, timing and delay before sampling. Our key finding was that time-lags between stressors led to longer-lasting effects. We also found that the sequential order of two stressors influenced effects on measures of ecosystem-level processes: for community respiration (CR) the metal-first sequence of stressors had a negative effect; for clearance rates the biocide-first sequence had the greater effect. Effects of stressors delivered simultaneously on CR and clearance rates were short-lived. Intra-individual effects on cellular viability did not correspond with effects on ecosystem-level variables. Results show that current frameworks for understanding and managing the effects of multiple stressors can be improved by incorporating temporal variation in both cause and effect.